Development of support based on chitosan and cellulose nanocrystals for the immobilization of anti-Shiga toxin 2B antibody. (15th March 2020) - Shankar, Shiv; Baraketi, Amina; D'Auria, Sabato; Fraschini, Carole; Salmieri, Stephane; Jamshidian, Majid; Etty, Marie Christine; Lacroix, Monique
Highlights: Membrane based on chitosan, cellulose nanocrystals, and glycerol was developed. Membrane was optimized for anti-Shiga toxin 2B antibody immobilization. Cellulose nanocrystals (0.6 %) & chitosan (95/2500) enhanced immobilization efficiency. Antibody immobilization optimized by fractional factorial and Box-Behnken designs. Membrane has detection limit of log 1 CFU/mL Escherichia coli O157:H7. Abstract: This work describes the development of membrane based on chitosan (CHI), cellulose nanocrystals (CNCs), and glycerol (GLY), and optimization of the formulation for immobilization of monoclonal anti-Shiga toxin 2B antibody (mAnti-stx2B-Ab) for E. coli O157:H7 detection. The effect of CHI deacetylation degree & viscosity, CNCs and GLY concentrations on Anti-stx2B-Ab immobilization efficiency was evaluated. Fractional factorial and Box-Behnken designs were applied to screen the effects of compounds interactions and optimize their concentrations for detection of Anti-stx2B-Ab. The results demonstrated that the use of 0.6 % (w/v) CNCs improved significantly the Anti-stx2B-Ab immobilization and the level of signal detection. The detection limit of Escherichia coli O157:H7 by developed optimized membrane is 1 log CFU/mL. The time needed for detection of E. coli O157:H7 was only 4 h of enrichment compared to 24 h with conventional methods. The developed immobilization support has potential for future pathogen detection in food and biomedical samples.